Determination of the latency effects on surgical performance and the acceptable latency levels in telesurgery using the dV-Trainer® simulator - Xu, Song; Perez, Manuela; Yang, Kun; Perrenot, Cyril; Felblinger, Jacques; Hubert, Jacques (Surgical endoscopy, 2014)
Background The primary limitation of telesurgery is the communication latency. Accurate and detailed data are lacking to reveal the latency effects on surgical performance; furthermore, the maximum acceptable latency in telesurgery remains unclear. Methods Sixteen medical students performed an energy dissection exercise and a needle-driving exercise on the robotic simulator dV-Trainer ® , and latencies varying between 0 and 1,000 ms with a 100-ms interval were randomly and blindly presented. Task completion time, instrument motion, and errors were automatically recorded. The difficulty, security, precision, and fluidity of manipulation were self-scored by subjects between 0 and 4 (0 the best, 2 moderate, and 4 the worst). Results Task completion time, motion, and errors increased gradually as latency increased. An exponential regression was fit to the mean times and motions ( R 2 > 0.98). Subjective scorings of the four items were similar. The mean scores were less than 1 at delays ≤200 ms, then increased from 1 to 2 at 300–700 ms, and finally approached 3 at delays above. In both exercises, latencies ≤300 ms were judged to be safe by all and 400–500 ms were accepted by 66–75 % of subjects. Less than 20 % of subjects accepted delays ≥800 ms. Conclusions The surgical performance deteriorates in an exponential way as the latency increases. The delay impact on instrument manipulation is mild at 0–200 ms, then increases from small to large at 300–700 ms, and finally becomes very large at 800–1,000 ms. Latencies ≤200 ms are ideal for telesurgery; 300 ms is also suitable; 400–500 ms may be acceptable but are already tiring; and 600–700 ms are difficult to deal with and only acceptable for low risk and simple procedures. Surgery is quite difficult at 800–1,000 ms, telementoring would be a better choice in this case.